Attractiveness and oviposition preference of Glycaspis brimblecombei Moore in Eucalyptus spp. - Pereira, Jaqueline Magalhães; Baldin, Edson Luiz Lopes [UNESP]; Soliman, Everton Pires [UNESP]; Wilcken, Carlos Frederico [UNESP] (Springer Nature, 2013)
The red gum lerp psyllid Glycaspis brimblecombei Moore (Hemiptera: Psyllidae) was first recorded in Brazil in 2003 and since then has caused serious damage in Eucalyptus forests. The damage is mainly due to defoliation, sooty mold and dieback, thus requiring the development of efficient management strategies. The settling and ovipositional preference of G. brimblecombei by species and clones of Eucalyptus were evaluated in free- and no-choice tests. Preliminary tests were done to determine the density of psyllid couples that produced the greatest densities of eggs, leaf position selection for oviposition, and whether oviposition was affected by preimaginal conditioning. Apical leaves were used more frequently for oviposition by the psyllid, and the number of eggs decreased from the apex to the base. The densities of 10 and 15 psyllid couples per seedling produced the highest oviposition. There was no evidence of preimaginal conditioning. In the free-choice test, E. grandis, E. urophylla, VM-1, I-144, C-219 and H-13 were less attractive to G. brimblecombei adults, with H-13, E. grandis and E. urophylla having the least oviposition. In the no-choice test, E. urophylla, GG-100 and E. grandis also demonstrated a lower oviposition, but E. camaldulensis and 3025 were highly susceptible. The low preference for the genotypes E. grandis and E. urophylla suggests the occurrence of a non-preference type resistance against the red gum lerp psyllid. Our results can be utilized for the development of management programs for G. brimblecombei in Eucalyptus forests. © 2012 Springer Science + Business Media B.V.
Keywords: Forest pest; Host plant resistance; Non-preference; Red gum lerp psyllid; Eucalyptus; Eucalyptus camaldulensis; Eucalyptus grandis; Eucalyptus urophylla; Glycaspis brimblecombei; Hemiptera; Psyllidae